Analisa Keandalan Jaringan Tegangan Menengah 13,8 KV Sebelum Dan Sesudah Sistem SCADA Di BOB PT.BSP-Pertamina Hulu Substation Zamrud - Wijaya, Puri; Lysbetti, Noveri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Analysis of reliability in this research using Section Technique method. The purpose of this research is to compare the value of the reliability index between before and after by using Supervisory Control and Data Acquisition (SCADA) System. SCADA is a computer-based equipment which is able to monitor the performance of a system in real time. According to method which is used by Section Technique by dividing a Distribution Network into a section, as each section is impacted same failure of interruption caused system shutdown. Steps to do this research are collecting data, calculate failure parameters, Perform the Reliability System Average Index Interruption Frequency Index (SAIFI) calculation. System Average Interruption Duration Index (SAIDI) and Custumer Average Interruption Duration Index (CAIDI). Index measurement results before SCADA in 2012 SAIFI = 0,891606 times a year, SAIDI = 2,184017 hours a year and CAIDI = 2,449533 hours a years. After SCADA in 2013 SAIFI = 0,466409 times a year, SAIDI = 1,070184 hours a years, and CAIDI = 2,294518 hours a year. With the SCADA system applied on the Zamrud Substation, Reliability Index has increased SAIFI = 58,9 %, SAIDI 51 % and CAIDI 6,34 %.Keywords : Section technique, SCADA, Distribution System, SAIFI, SAIDI, CAIDI